Odpowiedź :
Odpowiedź:
4,8+4x=6 to 4x=6-4,8 to 4x=1,2/:4 to x=0,3
-5-x=3,2 to -x=3,2+5 to -x=8,2/:-1 to x= -8,2
-3x+2=0,8 to -3x=0,8-2 to -3x= -1,2/:-3 to x=0,4
6-4x=4,8 to -4x=4,8-6 to -4x= -1,2 /:-4 to x=0,3
-5,3-2x=4,9 to -2x= 4,9+5,3 to -2x=10,2/:-2 to x=-5,1
0,5x+2,3=6 to 0,5x=6-2,3 to 0,5x=3,7 /:0,5 to x=7,4
0,4x-6=-4 to 0,4x= -4+6 to 0,4x=2 /:0,4 to x=5
-0,2x+0,3=4,3 to -0,2x=4,3-0,3 to -0,2x=4 /:-0,2 to x=-20
1,2-2,4x+1,2x= -4,8 to -2,4x+1,2x=-4,8-1,2 to -1,2x=3,6 /:-1,2 to x= -3
x-3,5x-2=8 to -2,5x=8+2 to -2,5x=10 /:-2,5 to x= -4
pozdrawiam
Odpowiedź:
1) 4.8+ 4x=6 | -4.8
4x=1.2 | :4
x=0.3
2) -5 -x =3.2 | -5
-x=-1.8
x=1.8
3)-3x+2=0.8 | -2
-3x=-1.2 | :-3
x=0.4
4)6-4x=4.8|-6
-4x=-1.2| : -4
x=0.3
5)-5.3-2x=4.9|+5.3
-2x=10.2|:-2
x=-5.1
6)0.5x+2.3=6|-2.3
0.5x=3.7|×2
x=7.4
dalej nie mam czasu sory